Analytical Investigation for Casson Nanofluid Model with the Influence of Viscous Dissipation - Rehman, Ali; İnç, Mustafa (Springer, 2024)
Analytical effects of viscous dissipation on time-dependent Casson nanofluid (CN) on a stretching surface are the focus of the current research. We used the proper transformations to change a set of PDEs into NODEs. This scheme is the homotopy analysis method (HAM). Graphs are used to plan the effects of various parameters on energy and momentum profiles, such as the magnetic parameter, nanoparticles volume friction unsteady parameter, parandtl number thermophoresis parameter, and Eckert number. In order to simulate and assess the structures of flow features, such as temperature and velocity profiles, in response to changes in developing factors, a physical description is utilized.
Keywords: Mathematica software; Stretching surface; CN; HAM; Viscous dissipation